2021
DOI: 10.1177/0014402921999310
|View full text |Cite
|
Sign up to set email alerts
|

Writing Scientific Explanations: Effects of a Cognitive Apprenticeship for Students With LD and English Learners

Abstract: In the current study, we examined the effect of cognitive apprenticeship with contextualized language instruction on students with LD (SWLDs) and English learners’ (ELs) ability to compose scientific explanations using a multiple-probe, multiple-baseline single-case design. Six middle school students (three in each subgroup) participated in ten 30-min sessions in an after-school program. The intervention was implemented with high fidelity, and all participants believed they benefited from the writing instructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…A recent study by Telesca et al (2020) demonstrated benefits in metalinguistic instruction (involving sentence combining and learning compare and contrast transition words) helped middle school students who struggled with literacy to better understand and express similarities and differences between related scientific concepts. A pilot study with SWDs shows promise for using a cognitive apprenticeship to integrate contextualized linguistic instruction with instruction in scientific reasoning (Lee & De La Paz, 2021). Students with LD and English language learners (ELLs) in that study wrote better mechanistic explanations with greater lexical sophistication and grammatical complexity after engaging in contextualized language activities that deconstructed language parts (nouns, verbs, adjectives, and prepositions) used to convey science ideas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study by Telesca et al (2020) demonstrated benefits in metalinguistic instruction (involving sentence combining and learning compare and contrast transition words) helped middle school students who struggled with literacy to better understand and express similarities and differences between related scientific concepts. A pilot study with SWDs shows promise for using a cognitive apprenticeship to integrate contextualized linguistic instruction with instruction in scientific reasoning (Lee & De La Paz, 2021). Students with LD and English language learners (ELLs) in that study wrote better mechanistic explanations with greater lexical sophistication and grammatical complexity after engaging in contextualized language activities that deconstructed language parts (nouns, verbs, adjectives, and prepositions) used to convey science ideas.…”
Section: Discussionmentioning
confidence: 99%
“…Students with attention and behavioral disabilities may also lack the goal setting and the self-monitoring skills needed to complete a complex writing task (Mason & Hedin, 2011; Boyle et al, 2016; Romine et al, in press). Students with cognitive, memory, or language disabilities may lack the required semantic and syntactic skills required for argumentative writing (Lee & De La Paz, 2021; Wissinger & De La Paz, 2020). Many SWDs who possess autism-like characteristics think literally and may struggle with abstract writing (Asaro-Saddler & Saddler, 2010).…”
Section: Literature Review: Argumentation In Science and In Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In half the studies, researchers took a linguistic view of language (see first row of Table 1). From this view, language was defined in terms of the named language(s) students knew and/or were developing proficiency in (González-Howard & McNeill, 2016; Licona & Kelly, 2020; Swanson et al, 2014), along with features of these named languages, like vocabulary terms (Relyea et al, 2022), lexical density (Symons, 2017), and language structures used for particular practices (González-Howard et al, 2017; Lee & Paz, 2021; Rodriguez-Mojica, 2019).…”
Section: Findings From the Literature Synthesismentioning
confidence: 99%
“…Researchers who took a linguistic view mostly focused on the practices of argumentation or explanation and, to a much lesser extent, on modeling. The main reason researchers offered for studying multilingual students’ experiences with argumentation and explanation was that these practices are more language-intensive, with speaking, writing, and reading described as the primary modes through which students sensemake and express ideas when engaged with these practices (e.g., González-Howard & McNeill, 2016; Infante & Licona, 2021; Lee & Paz, 2021; Rodriguez-Mojica, 2019). Meanwhile, researchers who shared an expansive view of language focused primarily on the practice of modeling and, to a lesser extent, on explanation or argumentation.…”
Section: Findings From the Literature Synthesismentioning
confidence: 99%